2010
DOI: 10.1021/nl904119y
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Atomic Contact between Pentacene and a Au Surface using Scanning Tunneling Spectroscopy

Abstract: We mapped spatially varying intramolecular electronic structures on a pentacene-gold interface using scanning tunneling spectroscopy. Along with ab initio calculations based on density functional theory, we found that the directional nature of the d orbitals of Au atoms plays an important role in the interaction at the pentacene-gold contact. The gold-induced interface states are broadened and shifted by various pentacene-gold distances determined by the various registries of a pentacene molecule on a gold sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Because both species are weakly adsorbed on the surface at a distance larger than 3.2 Å , the effects of registration site (A 3 at a hollow site and B 3 at a top site) is negligible. The observed different electronic characteristics exemplify that a subtle change of the molecular adsorption height (0.13 Å measured and 0.11 Å calculated) effectively modulates the molecular states [24]. Furthermore, we observed that some C molecules (denoted as C H ) have an apparent height higher than the normal C 3 molecules, as revealed in the line profile of Fig.…”
mentioning
confidence: 62%
“…Because both species are weakly adsorbed on the surface at a distance larger than 3.2 Å , the effects of registration site (A 3 at a hollow site and B 3 at a top site) is negligible. The observed different electronic characteristics exemplify that a subtle change of the molecular adsorption height (0.13 Å measured and 0.11 Å calculated) effectively modulates the molecular states [24]. Furthermore, we observed that some C molecules (denoted as C H ) have an apparent height higher than the normal C 3 molecules, as revealed in the line profile of Fig.…”
mentioning
confidence: 62%
“…18 Recently reported density functional theory (DFT) calculations for the organic semiconductor pentacene on an Au substrate gave similar results, suggesting orbital hybridization between pentacene and Au. 14 Figure 2c shows energy level diagrams for OTAP, OTAN, and Au. The HOMO levels for OTAP and OTAN are 5.53 and 5.34 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the TiO 2 anatase substrate does not significantly hybridize frontier molecular orbital states of pentacene in this adsorption configuration, in contrast to chemisorption on metallic substrates where significant orbital broadening and charge transfer were observed. [24][25][26] Bader charge analysis 27,28 revealed that pentacene transfers only 0.1 e − to the TiO 2 substrate.…”
Section: (E)mentioning
confidence: 99%